Efeito ansiolítico do composto piperazínico LQFM-030 em camundongos - Dias, Fernanda de Souza (2019)
Piperazine derivatives correspond to an extensive chemical class of compounds with therapeutic potential to act as anxiolytic, antipsychotic and antidepressant drugs. This study was performed to assess the effects of the new piperazinic derivative [1-(4-((1-(4-chlorophenyl)-1H-pyrazol-4-yl) methyl) piperazine-1-yl) ethanone] (LQFM-030) on the expression of behaviors that have been associated with anxiety disorders in the mouse species. Male Swiss mice were orally treated with LQFM-030 prior to predictive behavioral tests as open field, elevated plus-maze and light-dark box tests. In addition, an experiment was performed to assess if the prior systemic administration of flumazenil, a benzodiazepine site competitive antagonist, or NAN-190, a 5-HT1A competitive antagonist, was able to counteract the anxiolytic-like effect induced by the injection of LQFM-030. The treatment with LQFM-030 did not interfere with locomotor activity but enhanced time spent at the center of the open field, suggesting an anxiolytic-like effect of this compound. This activity was confirmed by the results obtained in the plus-maze and light-dark box tests, and it was counteracted after pretreatment with flumazenil and NAN-190. Altogether, these data revealed that LQFM-030 is a new piperazine derivative that has an anxiolytic-like profile in different mouse anxiety tests, and this activity seems to involve the participation of benzodiazepine and 5-HT1A receptors.